Prediction of size-dependent risk of salmon smolt (Salmo salar) escape through fish farm nets - Sistiaga, Manu Berrondo; Herrmann, Bent; Forås, Eskil; Frank, Kevin; Sunde, Leif Magne (Aquacultural Engineering, 2020)
The escape of small smolt through farm cage netting is a major challenge faced by the Norwegian salmon farming industry. Escape can occur when the smolt placed in the cages are smaller than the size estimated by the farmers. Furthermore, one may assume wrong mesh-properties as the cage netting change shape and/or state from stiff (mesh bars with tension) to slack (mesh bars without tension) due to sea currents or waves and become more suitable for penetration. The latter represents an increased risk for cages placed in more exposed sea areas, which is a growing trend in the industry due to increased demand for farming sites. The potential influence of mesh shape and state on the risk of escape from salmon farm cages is predicted. The morphological characteristics of salmon smolt are assessed and used to determine the risk of potential escape through meshes of different sizes, shapes and states. The results showed that fish smaller than 47 g and 201 g have the potential to escape through 30 mm and 50 mm meshes, respectively. In general, the risk of smolt escape is highest when the meshes in the netting are slack. Semi-slack meshes with mesh openness of between 65 and 95% also present a higher risk of smolt escape than square stiff meshes. The highest risk of escape was identified at approximately 80% mesh openness. This study illustrates the importance of mesh states in fish farming cage nettings. In many cases the minimum smolt size needed to maintain an escape risk below 1% was approximately twice as large for slack square meshes than for stiff square meshes of the same size.